News Construction: Framing Analysis of Jokowi's Political Dynasty Issue in Tempo Magazine (October 2023 – May 2024 Edition) - Putri, Aisyah Adinda; Widiastuti, Wahyu; Sari, Eka Vuspa (Jurnal Ilmu Sosial Mamangan, 2025)
Political dynasties are a phenomenon that often appears in political contexts. Political dynasties are power obtained in a primitive way, namely relying on the blood of a few people. The political dynastic system is basically a political strategy designed or built to gain power. This research looks at the issue of political dynasties that are considered to threaten democratic life in Indonesia. The media plays a role in shaping public opinion, news about political dynastic issues can be influenced by news partisanship and framing. Like Tempo mass media, the media highlights Jokowi's political dynasty through framing news that affects readers' perceptions. Using qualitative research methods and framing analysis from Robert N. Entman, this study reveals that Tempo magazine reports on how Jokowi's political dynasty is. The results of research in the October 2023 to May 2024 edition of Tempo magazine on the issue of political dynasties in online media in the current political period present a narrative that emphasizes the possibility of consolidation of power that has the potential to threaten democratic principles, strengthen oligarchy, and trigger public dissatisfaction with political continuity.